PENDAMPINGAN DALAM MEMBUAT SPT BADAN PADA PT NAYAKA ARTHA SADANA - Nawawi, Nataherwin; Angelika, Riska; Tio, Elisa (Jurnal Bakti Masyarakat Indonesia, 2024)
One of the tax obligations of SMEs is to file annual tax returns both as a corporate taxpayer and as an individual taxpayer. PT Nayaka Artha Sadana, as one of the MSMEs with a corporate NPWP, is required to file an annual corporate income tax return. PT Nayaka Artha Sadana employees are known to be unable to calculate the annual corporate income tax. This makes the online payment and filing of the CIT return difficult. Therefore, there is a need to provide assistance to the employees to be able to prepare a corporate income tax return. The purpose of this activity is to educate employees to have sufficient understanding of how to prepare or file the Corporate SPT in order to fulfill their tax obligations and provide precise and accurate information to the Tax Office. This activity starts with the preparation phase, i.e. the preparation of the data, then proceeds to the implementation phase and ends with the reporting phase. The community service team provided assistance through presentations, questions, and practice in the calculation and preparation of the annual corporate income tax return, starting with an explanation of income tax for corporations, preparation of the necessary document data, and simulating the calculation of income tax. This mentoring activity can improve taxpayers' understanding of taxes and benefits, which will encourage them to file and pay taxes voluntarily and on time ABSTRAK Salah satu kewajiban pajak UMKM adalah melaporkan SPT tahunan baik sebagai WP badan maupun sebagai WP orang pribadi. PT Nayaka Artha Sadana selaku sebagai salah satu UMKM yang memiliki NPWP badan, diwajibkan untuk menyusun SPT Tahunan PPh Badan. Karyawan PT Nayaka Artha Sadana, diketahui masih belum bisa menghitung PPh Badan tahunan. Hal ini menyebabkan pembayaran dan pelaporan SPT Badan secara online menjadi sulit untuk dilakukan. Oleh karena itu, diperlukan pendampingan kepada karyawan untuk dapat membuat SPT Badan. Kegiatan ini bertujuan untuk memberikan edukasi kepada karyawan agar memiliki pemahaman yang cukup mengenai pembuatan atau penyusunan SPT Badan agar dapat memenuhi kewajiban pajak mereka dan memberikan informasi yang tepat dan akurat kepada kantor pajak. Kegiatan ini dimulai dari tahap persiapan, penyiapan data-data, lalu dilanjutkan ke tahap pelaksanaan dan diakhiri dengan tahap pelaporan. Tim pengabdian masyarakat melakukan pendampingan dengan menggunakan presentasi, pertanyaan, dan praktik perhitungan dan penyusunan SPT Tahunan Badan, dimulai dengan penjelasan tentang pajak penghasilan bagi badan, penyiapan data dokumen yang diperlukan, dan simulasi penghitungan pajak penghasilan. Kegiatan pendampingan ini dapat meningkatkan pemahaman wajib pajak tentang pajak dan keuntungan yang akan mendorong mereka untuk melaporkan dan membayar pajak secara sukarela dan tepat waktu